Strategi Pedagogik Guru Pendidikan Agama Islam (PAI) dan Budi Pekerti dalam Internalisasi Literasi Digital Murid Generasi Alpha - Alfiah; Halimah, Nur; Rahmawati, Aslihatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Generation Alpha students at SMPN 3 Pakuhaji possess high digital proficiency yet face a character crisis in the virtual world (manifested in toxic speech, hoaxes, and diminished academic focus). This study aims to analyze the pedagogical strategies employed by Islamic Religious Education (PAI) and Character Education teachers to internalize digital literacy among Generation Alpha students at SMPN 3 Pakuhaji, Tangerang Regency. A qualitative field research method utilizing a case study approach was employed. Data collection involved four primary techniques: observation, interviews, documentation, and triangulation. The results indicate that the PAI teachers' pedagogical strategies are implemented by: (1) Integrating technology-based visual mediasuch as Smart TVs, projectors, YouTube videos, animations, and digital materialsto convey moral values ​​and make learning more engaging and varied; and (2) Instilling a culture of Tabayyun (verification) to counter hoaxes, providing guidance on finding credible religious websites, and reinforcing the concept of Muraqabah (awareness of God's constant presence) through lessons on faith and the practice of prayer (salat). The study concludes that these adaptive pedagogical strategies successfully fostered internal spiritual awareness among Generation Alpha students. This is evidenced by the development of a self-driven commitment to maintain digital etiquette, avoid social media conflicts, and shun negative content thereby upholding honesty and the fear of Allah SWT even without direct supervision. Furthermore, these adaptive strategies successfully bridged the learning gap and transformed digital devices from sources of distraction into tools for reinforcing noble character (akhlaqul karimah) within the digital space.